2018
DOI: 10.4049/jimmunol.1700542
|View full text |Cite
|
Sign up to set email alerts
|

Human NK Cells Downregulate Zap70 and Syk in Response to Prolonged Activation or DNA Damage

Abstract: The extent of NK cell activity during the innate immune response affects downstream immune functions and, ultimately, the outcome of infectious or malignant disease. However, the mechanisms that terminate human NK cell responses have yet to be defined. When activation receptors expressed on NK cell surfaces bind to ligands on diseased cells, they initiate a signal that is propagated by a number of intracellular kinases, including Zap70 and Syk, eventually leading to NK cell activation. We assayed Zap70 and Syk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…NKs integrate a variety of signals received through their activating and inhibitory receptors (Kruse et al., 2014, Vivier et al., 2008). The first steps of this pathway are fairly well known, including, for example, the signaling molecules DAP12, ZAP70, and Syk (Jelencic et al., 2018, Pugh et al., 2018), but the later stages are less understood. IFNG-AS1 can now join the web of intracellular signaling at this phase of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…NKs integrate a variety of signals received through their activating and inhibitory receptors (Kruse et al., 2014, Vivier et al., 2008). The first steps of this pathway are fairly well known, including, for example, the signaling molecules DAP12, ZAP70, and Syk (Jelencic et al., 2018, Pugh et al., 2018), but the later stages are less understood. IFNG-AS1 can now join the web of intracellular signaling at this phase of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study identified a subset of human NK cells that expressed low levels of the Zap70 and Syk kinases (Zap70 low Syk low ) and had decreased functional potential compared to Zap70 hi Syk hi NK cells. In addition, they showed that extended NK cell activation resulted in the loss of Zap70 and Syk (25). This suggests that extended NK cell activation leads to low levels of Syk and Zap70, resulting in decreased NK cell function.…”
Section: Resultsmentioning
confidence: 99%
“…However, to date, studies on the relationship between Syk and DNA breaks are limited. The only finding reported is that DNA damage and DNA double-strand breaks can suppress the expression of Syk in B [50] and NK cells [51].…”
Section: Discussionmentioning
confidence: 99%